NOVOSIBIRSK STATE UNIVERSITY IN THE LIGHT OF BIBLIOMETRICS (BY THE EXAMPLE OF THE GEOLOGY AND GEOPHYSICS DEPARTMENT) - Nikolay A. Mazov; Vadim N. Gureyev (Высшее образование в России)
The authors analyze publications of Geology and geophysics department of Novosibirsk State University and reveal trends in the development of science and education at the university. NSU shows the fastest growth in the number of publications that enabled it to improve performance in international university rankings. Good results can be explained by significant share of university staff which simultaneously works at scientific organizations of Siberian Branch of the Russian Academy of Sciences and since 2010 began to indicate NSU in paper affiliation. The most part of publications indexed in international bibliometric databases is published in Russian serials translated into English. However, fewer part ofpapers published in foreign international serials are more highly cited. NSU shows more active international collaboration in comparison with other Russian organizations in the field of Earth sciences. Furthermore, lists of graduates are studied in order to peruse performance of educational component in NSU. It was shown that more than half of graduates continue scientific work, and approximately 21 per cent defend Ph.D. theses in the nearest five years after graduation.